Structural Perspectives on Extracellular Recognition and Conformational Changes of Several Type-I Transmembrane Receptors - Chataigner, Lucas M. P.; Leloup, Nadia; Janssen, Bert J. C. (Frontiers in Molecular Biosciences, 2020)
Type-I transmembrane proteins represent a large group of 1,412 proteins in humans with a multitude of functions in cells and tissues. They are characterized by an extracellular, or luminal, N-terminus followed by a single transmembrane helix and a cytosolic C-terminus. The domain composition and structures of the extracellular and intercellular segments differ substantially amongst its members. Most of the type-I transmembrane proteins have roles in cell signaling processes, as ligands or receptors, and in cellular adhesion. The extracellular segment often determines specificity and can control signaling and adhesion. Here we focus on recent structural understanding on how the extracellular segments of several diverse type-I transmembrane proteins engage in interactions and can undergo conformational changes for their function. Interactions at the extracellular side by proteins on the same cell or between cells are enhanced by the transmembrane setting. Extracellular conformational domain rearrangement and structural changes within domains alter the properties of the proteins and are used to regulate signaling events. The combination of structural properties and interactions can support the formation of larger-order assemblies on the membrane surface that are important for cellular adhesion and intercellular signaling.